Simulation Possibilities of 3D Measuring in Progressive Control of Production - Drbul, Mario; Stancekova, Dana; Babik, Ondrej; Holubjak, Jozef; Gorogova, Ingrid; Varga, Daniel (Manufacturing Technology Journal, 2016)
The product price consists from several items. Time needed for adequate control of product is one of the most significant items, which can get expensive. So it is important, how the measurement strategy (measurement plan) is prepared. Time, which is not used for control of products by 3D measurement machine, is financial loss for company. This article deals with simulation of contact measurement, as a progressive tool, for preparation and creation of measurement plans for 3D coordinate measurement machines. Furthermore, the article deals with factors, that are not taken into account by offline programming during creation of measurement plan. Those can ultimately lead to significant difference between measurement simulation and measurement performed in workspace of measurement machines or CNC machines. This difference can cause serious shortcomings in measurement plans created in offline programming modules.
Keywords: Off-line programming; simulation measurement; coordinate measuring machine; CAD model